Endostar regulates EMT, migration and invasion of lung cancer cells through the HGF-Met pathway. (June 2019) - Shen, Yuyao; Chen, Qingwen; Li, Lihong
Abstract: Aim: Though Endostar (ES) could inhibit tumor growth by inhibiting tumor angiogenesis, other possible mechanisms have been less reported. This study aims to investigate the role of ES in the treatment of lung cancer from the perspective of macrophage-mediated epithelial mesenchymal transformation (EMT). Methods: THP1 cells were induced to polarized macrophages (MΦ). A549 and H1795 cells were separately treated with MΦ conditioned medium, ES (12.5 μg/ml) and HGF (5 ng/ml) for 24 h at 37 °C. Quantitative real-time polymerase chain reaction (qRT-PCR) was performed to detect the expression levels of CCL17, CD163, hepatocyte growth factor (HGF), Epidermal Growth Factor (EGF), transforming growth factor (TGF)-β1 and interleukin (IL)-6. Western blot was carried out to detect the p-MET, MET and EMT-related proteins (E-cadherin, N-cadherin, Snail and vimentin). Fibroblast-like A549 and H1975 cells were observed by a microscope. Cell invasion and migration were observed and analyzed by transwell and scratch assays. Results: The expression levels of CCL17 and CD163 were significant higher in MΦ. ES significantly inhibited the expression of HGF in MΦ. Moreover, ES could restore the abnormal expressions of EMT-related proteins and inhibit MΦ-induced and HGF-induced fibroblast-like lung cancer cells. Furthermore, ES suppressed the MΦ-induced and HGF-induced migration and invasion of lung cancer cells. ES was also found to down-regulate HGF-Met signaling in HGF-treated lung cancer cells. Conclusion: ES suppresses lung cancer progression by down-regulating HGF-Met signaling, revealing the possible mechanism of ES in the process of treating lung cancer patients. Highlights: Endostar inhibits lung cancer cells biological properties by the HGF-Met pathway.